Pengaruh Media Powerpoint Berbasis Audio Visual terhadap Minat Belajar Siswa - Zakaria, Muhammad Munif; Chandra, Aqlisty Nia; Suroningsih, Suroningsih (Journal of Elementary Education Research, 2023)
AbstractThis study aims to determine the effect of using audio-visual based powerpoint media on student interest in learning in class V MI Miftahul Falah Bodeh, especially in science subjects. The theoretical benefits of this research can add to the science of science learning and can develop the quality of education in the current era optimally using technology through audio-visual-based powerpoint media. While the practical benefits provide new insights in teaching about the importance of using learning media, for students to be more aware that the importance of using powerpoint media as a learning medium that helps students digest and understand the material presented in science lessons so as to increase student interest in learning. This type of research is an experiment with a quantitative approach that uses primary data as a source of research information data. This study used a one group pretest-posttest design. The data collection techniques used are questionnaires, observation, documentation. While the data analysis technique uses preliminary analysis, hypothesis analysis, and further analysis. The results showed that audio-visual based powerpoint media had an effect on the learning interest of grade V students in science subjects. The results obtained from the t-test are the value of ?ℎ????? which is 7.441 with a frequency (db) of 15 -2 = 13, at a significant level of 5% (0.05) obtained ?????? which is 1.771. So obtained ?ℎ????? ?????? = 7.441 1.771 which means H0 is rejected and H1 is accepted, so the hypothesis in this study is accepted, namely audio-visual based powerpoint media has an effect on the learning interest of grade V students in science subjects at MI Miftahul Falah Bodeh Pucakwangi Pati.